2015
DOI: 10.1016/j.biomaterials.2015.02.125
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced immunostimulatory effects of DNA-encapsulated peptide hydrogels

Abstract: DNA that encodes tumor-specific antigens represents potential immunostimulatory agents. However, rapid enzymatic degradation and fragmentation of DNA during administration can result in limited vector expression and, consequently, poor efficacy. These challenges have necessitated the use of novel strategies for DNA delivery. Herein, we study the ability of cationic self-assembling peptide hydrogels to encapsulate plasmid DNA, and enhance its immunostimulatory potential in vivo. The effect of network charge on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Gene therapy affords a promising way to treat congenital and acquired diseases [ 1 , 2 ]. Safe and efficient delivery of genetic material into target cells remains a challenging aspect of gene therapy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gene therapy affords a promising way to treat congenital and acquired diseases [ 1 , 2 ]. Safe and efficient delivery of genetic material into target cells remains a challenging aspect of gene therapy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self‐assembling peptides have been widely used as the extracellular matrix for regenerative medicine and as platforms to understand biological process and to screen important analytes . Pioneering work has also demonstrated that self‐assembling peptides can be used as self‐adjuvated vaccines through the covalent conjugation of peptide or protein antigens . However, the reported self‐assembling peptides, including L‐ and D‐peptides, cannot elicit strong CD8 + T‐cell responses.…”
mentioning
confidence: 99%
“…Supramolecular hydrogels [ 18 24 ] formed by self-assembly of small molecules in water, as demonstrated previously by us and other researchers, have numerous potential applications, such as encapsulation and delivery of DNA [ 25 ] and microRNA [ 26 ], delivery of therapeutic agents [ 27 – 29 ], scaffolds for cell culture [ 30 31 ] and spinal arthrodesis [ 32 ], sensor for detection of hyperuricemia disease [ 33 ] and diabetes [ 34 ], and matrix for the electrophoresis of acidic native proteins [ 35 ]. After obtaining the pure conjugates 1 – 8 , we tested their gelation properties.…”
Section: Resultsmentioning
confidence: 99%